The Great Masquerade: Identification of Clinically Relevant Clostridioides difficile Infections. (October 2020) - Sickbert-Bennett, Emily; Stancill, Lisa; DiBiase, Lauren; Alby, Kevin; Weber, David Jay
Abstract : Background: Despite clear guidance for appropriate testing of symptomatic patients for Clostridioides difficile testing (McDonald et al), the ideal testing methodology remains unresolved. Laboratories currently use different algorithms that incorporate enzyme immunoassay (EIA) testing for toxin, glutamate dehydrogenase (GDH) antigen, and polymerase chain reaction (PCR) testing in combination or as a single test. At UNC Hospitals, a large academic hospital with nearly 1, 000 beds in the ninth most populous state in the United States, patients are currently tested by an EIA test for toxin and GDH antigen first, and discordant toxin/GDH results are referred for PCR testing. Previous studies have demonstrated that detection of toxin by EIA is a better predictor of C. difficile infection (CDI) complications (Polage et al). Methods: We investigated all patients who were tested for C. difficile from July 2018 to June 2019. Within each testing methodology and result, we assessed the percentage of patients with at least 3 loose stools documented within a 24-hour period, percentage with a severe episode based on white blood cell (WBC) counts >15, 000 cells/mL, or percentage with a serum creatinine level >1.5 mg/dL. Fisher-type confidence intervals were calculated for each proportion. Results: Patients positive for C. difficile by the EIA method had 66.9% appropriate loose stool documentation (95% CI, 57.4%–75.5%), whereas patients with EIA-indeterminate (toxin negative, GDH positive) and positive by only PCR had 49.7% appropriate loose stool documentation (95% CI, 42.7%–56.8%). C. difficile patients that tested negative had 48.1% appropriate loose stool documentation (95% CI, 46.0–50.2%). In addition, patients positive by the EIA method had nearly double the proportion of severe disease by WBC or creatinine criteria compared to patients who were either positive by PCR or who tested negative (Table 1). Conclusions: Patients positive for C. difficile by the EIA method were statistically more likely to meet criteria for loose stool documentation. There was no statistically significant difference between patients that tested positive only by PCR or who tested negative. The percentage of patients with severe episode criteria based on WBC or creatinine was nearly doubled between those who tested positive by EIA and PCR (20% vs 10%), although this finding was not statistically significant. The percentage with severe disease (WBC or creatinine) was nearly identical among patients who were positive by PCR and who tested negative. These findings demonstrate that documentation of loose stool is a more sensitive indicator of toxin detection than either clinical parameter, reinforcing the importance of stool documentation in evaluating patients for C. difficile testing. Funding: None Disclosures: None